2001
DOI: 10.1044/1092-4388(2001/086)
|View full text |Cite
|
Sign up to set email alerts
|

Complex Syntax Production of African American Preschoolers

Abstract: This study examined changes in the complex syntax production of 85 3- and 4-year-old African American children and the role of child (i.e., gender, age, African American English) and family (i.e., home environment) factors. The mean percentage of utterances containing one or more complex syntax forms was 6.2% at 3 years and 11.7% at 4 years. Girls produced more complex syntax forms than did boys. Complex syntax production increased significantly between age 3 and age 4 and correlated positively with mean lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…Finally, a number of AAE studies have shown that children vary in the rate (i.e., density) at which they produce nonmainstream grammatical structures (Craig, Zhang, Hensel, & Quinn, 2009;HortonIkard et al, 2005;Jackson & Roberts, 2001;Kohler et al, 2007;Oetting, 2005;Oetting et al, 2010;Pruitt & Oetting, 2009;Terry, Connor, Thomas-Tate, & Love, 2010;Van Hofwegen & Wolfram, 2010). However, the relationship between children's nonmainstream dialect densities and their use of individual grammatical structures is unclear.…”
Section: Previous Studies Of Child Aaementioning
confidence: 93%
See 2 more Smart Citations
“…Finally, a number of AAE studies have shown that children vary in the rate (i.e., density) at which they produce nonmainstream grammatical structures (Craig, Zhang, Hensel, & Quinn, 2009;HortonIkard et al, 2005;Jackson & Roberts, 2001;Kohler et al, 2007;Oetting, 2005;Oetting et al, 2010;Pruitt & Oetting, 2009;Terry, Connor, Thomas-Tate, & Love, 2010;Van Hofwegen & Wolfram, 2010). However, the relationship between children's nonmainstream dialect densities and their use of individual grammatical structures is unclear.…”
Section: Previous Studies Of Child Aaementioning
confidence: 93%
“…For example, for 37 children between the ages of 3 and 4 in the SALT 2012 reference database (Miller & Iglesias, 2012), the average MLU was 3.61 (SD = .55; range = 2.62-4.65). In a study of African American children, Jackson and Roberts (2001) reported the mean MLU of 3-year-olds to be 3.62 (SD = .56).…”
Section: Language-sampling Proceduresmentioning
confidence: 96%
See 1 more Smart Citation
“…Gender-dependent differences seem to exist only in younger children, up to 3 or 4 years old. Girls present higher MLU-w than boys and they also produce more complex syntactic forms 23,25 . Therefore it is possible to claim that at around age 4 syntactic development has already acquired a certain stability, thus evening out the gender differences that may exist until that age.…”
Section: (Talc) This Test Encompasses Comprehensionmentioning
confidence: 99%
“…At schooling age girls also seem to be more successful in all verbal competences than boys 21 . Regarding MLU, no gender differences are usually observed 22 , although there are some different results, indicating a better performance of girls, though only until the age of 3 or 4 [23][24][25] .…”
Section: Conflict Of Interest: Non-existentmentioning
confidence: 99%